Walking speed as an aging biomarker in baboons (Papio hamadryas). Issue 6 (28th September 2015) - Huber, Hillary F.; Gerow, Kenneth G.; Nathanielsz, Peter W.
Abstract: Background: Walking speed is an important human aging biomarker. Baboons are valuable translational models for aging studies. Establishing whether walking speed is a good aging biomarker has value. We hypothesized there would be characteristic age‐related decline in baboon walking speed. Methods: We studied 33 female baboons aged 5–21 years. Walking speed was calculated by the time to walk between landmarks separated by known distances. A regression model was developed to describe the relationship between speed, age, and body weight. Results: Speed negatively associated with age, a relationship enhanced by increased weight ( P < 0.0005). For 16‐kg animals, speed declined approximately 0.6 cm/s yearly. For each additional kilogram of weight, speed declined an additional 0.3 cm/s yearly. Conclusions: Baboon walking speed declines with age, an effect modulated by weight. Ease of measurement and strong age association make walking speed a valuable biomarker for aging research with this important experimental species.